Advanced simulation of a 750 t/d municipal solid waste grate boiler to better accommodate feedstock changes due to waste classification. (1st September 2022) - Gu, Tianbao; Ma, Wenchao; Berning, Torsten; Guo, Zhenning; Andersson, Ronnie; Yin, Chungen
Abstract: To better accommodate changes in municipal solid waste (MSW) properties due to waste classification, advanced computational fluid dynamics (CFD) simulations are carried out for a 750 t/d MSW moving-grate boiler. A moving-grate bed model is developed and iteratively coupled to the freeboard simulation which is performed in Ansys Fluent. The model is first validated by the measurement data for the daily operation case incinerating current feedstock. Then, the model is deployed to investigate the impacts of feedstock change and adjust boiler operation for better accommodating the new MSW. The results indicate incineration of the new MSW leads to irrational utilization of oxygen, non-uniform temperature distribution and low mixing, while maintaining current operation conditions. Subsequently, adjustments of air supply and thermal input are proposed and conducted by the model, which address the potential issues and benefit boiler operation and energy recycling. Finally, the uniformity of velocity and turbulent kinetic energy which indicates mixing, are compared for different cases. The latter is increased by 51.39% and 81.04% after the adjustments of air supply and thermal input. The investigation provides solid references for incinerating new MSW in the current boiler.